2014
DOI: 10.1007/s00213-014-3716-x
|View full text |Cite
|
Sign up to set email alerts
|

Can Valeriana officinalis root extract prevent early postoperative cognitive dysfunction after CABG surgery? A randomized, double-blind, placebo-controlled trial

Abstract: We concluded that, based on this study, the cognitive state of patients in the valerian group was better than that in the placebo group after CABG; therefore, it seems that the use of V. officinalis root extract may prevent early postoperative cognitive dysfunction after on-pump CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…This changes in the public mood might have influenced the results, as all assessments took place after May 1, 2014. Recent studies have suggested that valerian is less promising as a sleep aid than earlier studies suggested (Leach & Page, ), but other clinical benefits of valerian are still supported by recent randomized, placebo‐controlled trials (Ahmadi et al, ; Hassani et al, ; Jenabi, Shobeiri, Hazavehei, & Roshanaei, ). Further studies are needed to confirm valerian's efficacy in various clinical populations and determine the optimal dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This changes in the public mood might have influenced the results, as all assessments took place after May 1, 2014. Recent studies have suggested that valerian is less promising as a sleep aid than earlier studies suggested (Leach & Page, ), but other clinical benefits of valerian are still supported by recent randomized, placebo‐controlled trials (Ahmadi et al, ; Hassani et al, ; Jenabi, Shobeiri, Hazavehei, & Roshanaei, ). Further studies are needed to confirm valerian's efficacy in various clinical populations and determine the optimal dose.…”
Section: Discussionmentioning
confidence: 99%
“…Valerian's effects might be too modest to detect with multidimensional scales. Additional measures of cognitive function (Hassani et al, ) could help identify valerian's clinical benefits in future studies. In addition, study period might be insufficient to produce improvement in anxiety, and low dose‐VRE might require extended treatment course lasting longer than 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of recent prospective studies, it has been demonstrated that cognitive impairment after CABG is reversible in a significant part of patients and the majority of patients revert to the initial cognitive status within three to twelve months after surgery (Hassani, Alipour, Darvishi Khezri, Firouzian, Emami Zeydi, Gholipour Baradari, Ebrahim Zadeh, 2015). However, in 42% of patients cognitive impairment persists beyond 5 years after CABG.…”
Section: State Of the Problemmentioning
confidence: 99%
“…Healthful eating patterns such as the Mediterranean diet, have been shown to offer protective effects on brain function, such as memory and cognitive processes (5,6). A growing number of data indicates that native Mediterranean herbs and spices are within those components of the Mediterranean diet involved in memory and cognitive enhancement (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%